STUDY ON SOIL STABILIZATION WITH CEMENT AND ADDITIVES AS BASE LAYER FOR ROAD PAVEMENT (CASE STUDY : SOIL FROM NUSANTARA CAPITAL CITY AREA) - Siona Tana, Anglin
The massive construction of the Nusantara Capital City (IKN) has led to a significant increase in the demand for aggregates. To ensure the continuous development of IKN, aggregates are being supplied from outside the island, which increases construction costs, including road construction costs. To reduce aggregate demand and construction costs, one potential solution is to use alternative base layer materials such as soil cement base (SCB). Local soil materials have good bearing capacity and are widely available, making SCB a viable option for road pavement. A mixture of soil and cement alone may not always provide the necessary properties for a base layer for road pavement. Adding additives to the soil-cement mixture can improve its properties to meet the requirements for a base layer. This research aims to study the stabilization of soil from the Nusantara Capital City with cement and additives for use as a base layer for road pavement. Soil samples from the Nusantara Capital City are dark brown coarse-grained soils dominated by the sand fraction (75.92%). They are classified as SM (Silty Sand) with a fine content of less than 50% (23.30%), low acidity (pH 6.32), low sulfate content (0.007356%), and free of organic matter. These properties make the soil suitable for use as a soil-cement mixture. The mixture was designed using 13-15% cement and 1-3% additives. Unconfined Compressive Strength (UCS) and Wetting- Drying tests were conducted on all variations of the soil-cement mixture, both with and without additives. The test results were used to evaluate the strength and durability of all mixture variations according to the technical requirements for a base layer. Pavement structure and construction cost analysis were performed to evaluate the construction cost per vehicle axle to obtain an economical mixture. Based on the strength analysis, all variations of the mixture, both soil-cement mixtures (13-15%) without additives and with additives (1-3%), showed 7-day compressive strength values higher than the target compressive strength value (2400 kPa). This indicates that they meet the strength requirements for a base layer for road pavement. At curing ages of 3 and 7 days, the soil-cement mixture without additives had higher compressive strength than the soil-cement mixture with additives. However, at 28 days of curing, the soil-cement mixture with additives had higher compressive strength than the soil-cement mixture without additives. The soil-cement mixture with 1%, 2%, and 3% additives showed 9.6%, 6.7%, and 12.9% higher 28-day compressive strength, respectively, compared to the soilcement mixture without additives. Based on the durability analysis, the soil-cement mixture without additives showed high weight loss, indicating that it does not meet the durability requirements for a base layer for road pavement. The soil-cement mixture without additives had low resistance to wet-dry cycles, with the highest weight loss of 15.90% at a cement content of 13% and the lowest of 13.74% at a cement content of 15%. On the other hand, the soil-cement mixture with additives showed a weight loss of around 7%, meeting the durability requirements for a base layer for road pavement. The soilcement mixture with 1%, 2%, and 3% additives showed 55%, 46%, and 57% lower weight loss, respectively, compared to the soil-cement mixture without additives. The minimum cement content that resulted in a target compressive strength of more than 2400 kPa was 13%. The minimum additive content that resulted in a weight loss of less than 7% was 1%. Therefore, the optimum cement content and optimum additive content were 13% and 1%, respectively. Based on the cost analysis per vehicle axle, the mixture of 13% cement and 1% additive was the optimum mixture as it resulted in the lowest cost per axle, which was 0.033 Rp/m2/ESA. This mixture provides the best combination of low cost and adequate performance. The use of a 13% cement and 1% additive soil mixture as a base layer for road pavement can save up to 53.4% of the road construction cost compared to pavements using granular base layers. Soil-cement base (SCB) can serve as a viable alternative to granular base layers in road pavements. SCB offers several advantages, including lower cost, increased strength, and enhanced durability, which can reduce aggregate requirements and construction costs. The implementation of SCB in road pavements can promote more economical construction and lead to lower maintenance costs. This aligns with the goal of sustainable development for the Nusantara Capital City.